Pendugaan umur simpan kerupuk sagu goreng dengan pendekatan kurva isoterm sorpsi air [Shelf-life estimation of fried sago crackers by water sorption isotherm curve approach] - Ayu, Dewi Fortuna; Situmorang, Budi Lambok; Efendi, Raswen; Juarsa, Rahmadini Payla (Teknologi Hasil Pertanian Fakultas Pertanian Universitas Lampung, 2024)
Fried sago crackers are dry local foods easily damaged by moisture during storage. To increase economic value and open commercialization opportunities, a study aimed to estimate the shelf life of white and red fried sago crackers using an acceleration method based on the water sorption isotherm curve. Estimating the shelf life was carried out by storing crackers in several modified jars containing different saturated salt solutions. Calculating the moisture permeability constant of polyethylene and polypropylene packaging was also carried out to support the necessary data. The results showed that sago crackers packaged in polypropylene had a longer shelf life than polyethylene plastic. The white sago crackers with polypropylene plastic had a shelf life of 19.89-69.83 days at 70-90% RH, while polyethylene was 12.02-42.21 days at 70-90% RH with 0.0434 g H2O.g solid-1 critical water content. The red sago crackers with polypropylene plastic had a shelf life of 18.26-69.93 days at 70-90% RH, while polyethylene was 11.04-42.27 days at 70-90% RH with a critical water content of 0.0455 g H2O.g solid-1. The chosen model for the water sorption isotherm curve was Hasley and GAB, with equation log (ln (1/aw)=-1.82-1.31 log Me for white sago fried crackers and Me=(0.5157aw)/(1-0.9632aw)(1+15.578aw) for red sago fried crackers, respectively. Fried sago crackers in polypropylene plastic packaging have the potential to be developed as local food products with a longer shelf life.